Mutual Diffusivities of Binary Mixtures of Water and Poly(ethylene) Glycol from Heterodyne Dynamic Light Scattering - Wu, Wenchang; Supper, Malvina; Rausch, Michael Heinrich; Kaspereit, Malte; Fröba, Andreas Paul (International Journal of Thermophysics, 2022)
In the present study, the mutual diffusivity D11 in binary mixtures of water with technical polydisperse poly(ethylene) glycol (PEG) blends with molar masses of (1000, 4000, or 6000) g⋅mol−1 as well as with a purified monodisperse PEG homolog with a polymerization number of 21 and a molar mass of 943 g⋅mol−1 was investigated by heterodyne dynamic light scattering (DLS) as a function of temperature and/or PEG concentration. The measured D11 for technical PEG 1000 and pure PEG 943 match within the experimental uncertainties and agree well with the available literature data. D11 decreases with increasing molar mass of the PEGs at constant temperature and weight fraction. For the technical PEG 4000, it could be shown that D11 increases with increasing temperature and exhibits a nonlinear concentration dependence. This study demonstrates that heterodyne DLS can be applied for the reliable determination of D11 of aqueous solutions of PEGs over a broad range of PEG weight fractions from 0.01 up to the solubility limit with an average expanded uncertainty (k = 2) of 5.5 %. Moreover, the results show that monodisperse PEGs are suitable model systems for studying the diffusion behavior of bimodal and also multimodal particulate systems.
CRIS-Team Scopus Importer:2022-10-21
Keywords: Chromatography; Dynamic light scattering; Monodisperse; Mutual diffusivity; Poly(ethylene) glycol